2012
DOI: 10.1155/2012/501705
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Cystadenomas: A Case for Complete Resection

Abstract: Introduction and Objective. Biliary cystadenoma is a rare benign neoplasm of the liver with less than 200 cases being reported allover the world. We report a series of 13 cases highlighting the radiological findings and problems related to its management. Materials and Methods. Records of thirteen patients who underwent surgery for biliary cystadenomas, between March 2006 and October 2011, were reviewed retrospectively. Results. Majority of the patients were females (11 out of 13), with a median age of 46 (23–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Many patients with BCT will be asymptomatic; other patients with BCT can present with non-specific symptoms, most commonly abdominal pain and distention (55-90%). (3, 7, 11, 17, 18, 23) While laboratory values are normal in most patients, approximately 20% of patients present with elevated liver function tests such as an abnormal bilirubin level. (19, 24) Obstructive jaundice and cholangitis are rare and do not correlate with malignant disease and typically occur with extrahepatic BCT.…”
Section: Presentation and Differential Diagnosis Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many patients with BCT will be asymptomatic; other patients with BCT can present with non-specific symptoms, most commonly abdominal pain and distention (55-90%). (3, 7, 11, 17, 18, 23) While laboratory values are normal in most patients, approximately 20% of patients present with elevated liver function tests such as an abnormal bilirubin level. (19, 24) Obstructive jaundice and cholangitis are rare and do not correlate with malignant disease and typically occur with extrahepatic BCT.…”
Section: Presentation and Differential Diagnosis Considerationsmentioning
confidence: 99%
“…(34, 36) Some authors now advocate classifying BCT with biliary tree communication and no ovarian stroma as biliary IPMNs. (23, 35-37) In one study, Zen et al (35) identified 9 cases of BCT noting 5 tumors with direct communication to the biliary tree. None of these 5 cases contained ovarian-like stroma and all had different clinicopathologic characteristics than BCT.…”
Section: Presentation and Differential Diagnosis Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for these observations may be that the apoptotic rate of epithelial cells has been shown to be positively correlated with the degree of duct damage, highlighting the essential role of cell apoptosis and relevant markers thereof in the progression of this disease. Cystic-shaped CCCs are characterized by relatively large sizes and thick cyst walls, with moderate to large numbers of elastic and reticular fibers (Ahanatha Pillai et al, 2012). In contrast, fusiform-shaped CCCs are relatively smaller and have thinner walls without elastic or reticular fibers (De and Basu, 2007).…”
Section: Discussionmentioning
confidence: 99%